2022
DOI: 10.1265/ehpm.21-00044
|View full text |Cite
|
Sign up to set email alerts
|

Association between daily ambient temperature and drug overdose in Tokyo: a time-series study

Abstract: Background: Previous studies have reported that high ambient temperature is associated with increased risk of suicide; however, the association has not been extensively investigated with drug overdose which is the most common method of unsuccessful suicidal behavior in Japan. Therefore, this study aims to examine the short-term association between daily mean temperature and the incidence of self-harm attempts by drug overdose in Tokyo, Japan. Methods: We collected the emergency ambulance dispatch data and dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This is consistent with a broader body of existing studies investigating the association between ambient temperature and suicide in terms of relative risk in Japan [16,17,36]. Our findings are also consistent with a previous study in Tokyo, Japan, which indicated that an increase in daily mean temperature was nonlinearly associated with an increased risk of drug overdose, the most common method of unsuccessful suicide attempts in Japan [37]. Our findings also align with previous studies that showed higher relative risks for older people and women in Japan [16,17].…”
Section: Comparison With Other Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with a broader body of existing studies investigating the association between ambient temperature and suicide in terms of relative risk in Japan [16,17,36]. Our findings are also consistent with a previous study in Tokyo, Japan, which indicated that an increase in daily mean temperature was nonlinearly associated with an increased risk of drug overdose, the most common method of unsuccessful suicide attempts in Japan [37]. Our findings also align with previous studies that showed higher relative risks for older people and women in Japan [16,17].…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…Our findings also align with previous studies that showed higher relative risks for older people and women in Japan [16,17]. Similarly, the previous study investigating the association between daily mean temperature and drug overdose using emergency ambulance dispatch data in Tokyo also found higher relative risks among older people and women [37]. However, the results from a multi-country study showed that the observed differences by sex and age group, with nonoverlapping confidence intervals, occur only in Japan and South Korea [16].…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…In addition, opening windows on hot nights may increase noise-related stress, resulting in reduced quality of sleep (Murage et al 2017). Sleep deprivation or being awake at night due to hot nights can increase the use of alcohol or other substances, and social support declines during the night (Perlis et al 2016, Roy et al 2022. Furthermore, staying awake at night may decrease frontal lobe function, leading to diminished problem-solving abilities and increased impulsive behaviors (Perlis et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As night-time heat can cause sleep disorders or sleep deprivation (Van Someren 2003), which potentially leads to an increase in the risk of suicide (Perlis et al 2016, Roy et al 2022, we hypothesized that districts, where people sleep less, have a higher risk of suicide for exposure to night-time heat. We tested this hypothesis by adding an interaction term between the hot night indices and the mean sleep hours (low vs. high) of each district in the model.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing concerns about anthropogenic greenhouse gas emissions catalyzing the changes in global climate, health consequences arising from temperature have gained significant attention. Previous studies have found temperature adversely affected cardiovascular diseases [ 1 , 2 ], suicidal behavior [ 3 ], overall mortality [ 4 , 5 ] and other related outcomes [ 6 ]. Given that the respiratory system is directly and significantly influenced by temperature, its effects have been of greater concern than other systems.…”
Section: Introductionmentioning
confidence: 99%